Thiodiketopiperazines with two spirocyclic centers extracted from Botryosphaeria mamane, an endophytic fungus isolated from Bixa orellana L. (February 2019) - Barakat, Fatima; Vansteelandt, Marieke; Triastuti, Asih; Jargeat, Patricia; Jacquemin, Denis; Graton, Jérôme; Mejia, Kember; Cabanillas, Billy; Vendier, Laure; Stigliani, Jean-Luc; Haddad, Mohamed; Fabre, Nicolas
Abstract: Three thiodiketopiperazines, botryosulfuranols A-C(1 –3) were isolated from the endophytic fungus Botryosphaeria mamane . The three compounds present sulfur atoms on α- and β- positions of phenylalanine derived residues and unprecedented two spirocyclic centers at C-4 and C-2′. Their planar structures were determined by spectroscopic analysis and absolute configurations were achieved by X-ray diffraction analysis and ECD and NMR chemical shifts calculations. Botryosulfuranol A (1 ) was the most cytotoxic compound against four cancer cell lines (HT-29, HepG2, Caco-2, HeLa) and two healthy cell lines (IEC6, Vero) highlighting the importance of an electrophilic center for cell growth inhibition. Graphical abstract: Three undescribed thiodiketopiperazines exhibiting two spirocyclic centers were extracted from the culture of the endophytic fungus Botryosphaeria mamane isolated from Bixa orellana leaves. Highlights: Three thiodiketopiperazines were isolated from Botryosphaeria mamane. These alkaloids possess unprecedent spiro[isoxazolidino-cyclohexenone] scaffold. Botryosulfuranol A inhibited the growth of both cancer and healthy cell lines.